THE CHARACTERISTICS OF PREGNANT WOMEN WHO HAVE HEMOGLOBIN LEVEL BELOW NORMAL - Mayangsari, Mulia (NHM PRESS, 2085)
Hemoglobin is a protein that is rich in iron. It has an affinity (combiningpower) with oxygen and with oxygen it forms oxihemoglobin in red blood cells.Based on the result of preliminary study conducted at the PonkesdesMoarahKlampis Bangkalan, data was obtained in September pas November 2018with 47 pregnant women, with 23 (48.9%) cases of pregnant women. The purposeof this study is to determine the characteristics of the human, parity andnutritional patterns in pregnant women who have hemoglobin levels belownormal. This research method used descriptive. Independent variables namely age,parity, nutritional pattern and the dependent variable was the level of hemolgobinbelow normal. The study population were all pregnant women who had a normalhemoglobin level of 30 pregnant women. Data collection using questionnaires.Processing data using a computer using editing, coding and tabulatingtechniques. Data analysis using frequency distribution tables. This reseach hasbeen carried out ethical clearance test by KEPK STIKes Ngudia Husada Madura.The results of the study at age showed <20 years (46.7%), at parity showedprimipara and multipara (43.3%) and nutritional patterns (50%). It is expected that midwives will increase HE to pregnant women who have thepotential to have hemoglobin levels below normal by looking at age, parity andnutritional patterns. Pregnant women pay more attention to nutritional patternsbecause pregnant women who have below normal hemoglobin levels (anemia)will have an effect on fetal growth and development.